2009
DOI: 10.1111/j.1440-1827.2009.02403.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin, Bcl‐2 and microvessel density in normal, hyperplastic and neoplastic endometrium

Abstract: Adrenomedullin (ADM) is a multifunctional 52-amino acid peptide involved in numerous physiological and pathological processes, including angiogenesis, growth regulation, differentiation, and vasodilation. ADM is thought to act through the G protein-coupled receptor calcitonin receptor-like receptor, with specificity being conferred by receptor-associated modifying protein 2. The aim of the present study was to clarify the roles of ADM status, and tumor vessels in endometrium. Specimens were examined for ADM, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Altogether 20 observational studies with a total of 1,278 specimens (137 proliferative endometrium, 676 endometrial hyperplasia, and 465 endometrial cancer), were included in the systematic review. The flow diagram reporting the process of study selection is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Altogether 20 observational studies with a total of 1,278 specimens (137 proliferative endometrium, 676 endometrial hyperplasia, and 465 endometrial cancer), were included in the systematic review. The flow diagram reporting the process of study selection is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Subjectively, NBI provided clearer visualization of the NL than did white light, especially the delicate capillary architecture and angiogenesis (Fig. 2), which are considered essential for the development of neoplasms, including EC and atypical hyperplasia [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…The first role is regulation of the brain circulation: in the physiological state, trace amounts of ADM in the plasma adjust the basilar vascular tension together with nitric oxide, prostacyclin, endothelin-1, and other vasoactive substances [12]. An experiment [13] confirmed that ADM in cerebral arteries of dogs and cats has a strong vasodilating effect, and it can regulate and maintain cerebral blood flow. The mechanism may be related to increased intracellular cAMP concentration and increased endothelial nitric oxide production [14].…”
Section: Discussionmentioning
confidence: 99%